Kekuatan Faktor Kualitas Layanan Pada Kepuasan: Perspektif Mahasiswa Perguruan Tinggi Jarak Jauh - Shari, Risna; Anita, Andi Suci; Ibandong, Ibandong (Ekonomis: Journal of Economics and Business, 2024)
Student satisfaction in Open Distance Learning is an indicator of the success of educational delivery. The aim of this research is to identify significant factors influencing student satisfaction in distance learning at Open University. The modified SERVQUAL Service Quality model is used in this study. The independent variables in this research include Assurance, Empathy, Responsiveness, Reliability, and Website Content, while the dependent variable is Student Satisfaction. Data was collected through self-administered questionnaires from 244 management students at Open University. The analysis is based on descriptive and inferential statistics. The research results indicate that Assurance, Reliability, and Website Content are statistically significant factors associated with student satisfaction, and these findings can contribute to improving the quality of distance learning service processes.